(untitled) (Third Sector Social Economic Review, 2012)
There is a desire to imitate developed countries in the world. Developing countries, underdeveloped countries and undeveloped countries directly want to be like developed countries instead of searching how they succeeded in become a developed country. When we make a research about developed countries, they all have mutual aid, public spirit, combination, and cooperation teories in origin. These teories are actually basic factors of cooperative trading system. We all know that we will go thorough hard times to be in a good position in this sector. As Seyh Edebali, the mentor of Osman Bey who was founder of Ottoman Empire, said “ High degree people have much more enemies. “ , we understand this speech very well now. On the other hand it is possible to come up with a theory “ Lower degree people may have more enemies. “ Developed countries are following a certain political policy to keep their positon in safe by forcing or destroying developing and underveloped countries. Cooperatives are organizations that help countries growth and developing when it is used in a country. They have a lot of effects and maybe the most important one is social ones. Social effects are explained in details in article. It may be good source of staff for cooperatives by helping disabled people socialize and their rehabitions and helping them to reach their aims.